1965
DOI: 10.1002/bip.360030301
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and equilibria in the acid denaturation of deoxyribonucleic acids from various sources

Abstract: SynopsisThe acid deiisturat,ioii trf :I vsriet,y of 1)NAl samples wit.11 guanine -cytosine (GC) conte~its ranging from 3744% hns been investigated by means of potentiometric, spectrophot,ometric, and thermal titrations, including spect.rophotonietric titrations in a stopped-flow fast reaction apparatus. As the pH of a solution of native UN.4 is lowered from the neutral range the net charge oil the mylecule becomes more positive as a result of the addition of protons to the bases adeuine, cytosine, and to a les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

1966
1966
1994
1994

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…This increase is small for individual nucleotides and denaturated DNA It is more significant for helical DNA characterized by high charge density. pK 2 G = 3.7 was determined for O.lM NaCl in (14). In the present study, the concentration of N a+ is equal to 0.195M.…”
Section: Experimental Data and Results Of Calculation For Acidic Mediummentioning
confidence: 84%
See 1 more Smart Citation
“…This increase is small for individual nucleotides and denaturated DNA It is more significant for helical DNA characterized by high charge density. pK 2 G = 3.7 was determined for O.lM NaCl in (14). In the present study, the concentration of N a+ is equal to 0.195M.…”
Section: Experimental Data and Results Of Calculation For Acidic Mediummentioning
confidence: 84%
“…In (12,13) the pK value of cytosine was estimated directly in melted DNA regions. One can estimate the pK 2 G (pK of guanine of bonded base pairs) using the results of(l2, 14). According to them pK 2 G-3.7 (index 1 relates to melted regions, and index 2 relates to helical ones).…”
Section: Experimental Data and Results Of Calculation For Acidic Mediummentioning
confidence: 99%
“…This is done most directly by heat-capacity measurements, which have not yet been extensively employed (153). The most thorough studies are those of Bunville et al (108) the acid denaturation of DNA. It is necessary to take into account the contribution of the heat of ionization of the bases in determining the heat of DNA denaturation by acid.…”
Section: Ex~'m~i~entmentioning
confidence: 99%
“…Recent calorimetric measurements made by Bunville et af. [17] and also by Privalov et ul. [18] showed that the average value of A H for denaturation was close to 9 kcal/mol base pairs (37.6 kJ/mol) at neutral pH.…”
Section: Thermodynamic Charucteristics For Conformational Reaction Ofmentioning
confidence: 83%